Rekonstruksi Teologi Kesetaraan Gender dalam Pemikiran Fatimah Mernissi dan Mansour Fakih - Azkia Faiqotun Ni’mah; Muhamad Aldi; Farichatul Maftuchah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
Gender inequality in Islamic societies often stems from patriarchal interpretations of religious texts. This research aims to analyze and compare the gender liberation theology of two prominent Muslim intellectuals, Fatimah Mernissi and Mansour Fakih. Utilizing a literature study method with comparative and critical analysis approaches, this study explores how both figures deconstruct the roots of gender inequality. The findings reveal that Fatimah Mernissi emphasizes her struggle on epistemological and historical-philological critiques of misogynistic hadiths, which she identifies as products of